Synthesis, spectroscopy and electrochemistry of mono and dinuclear complexes of a peripherally mixed ligand and the interaction of (E, E) Ni(LH)(2) with Pd2+ and Ag+ - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2003)
We describe the synthesis, characterization and electrochemistry of a new family of peripherally functionalised vicdioxime, 5,6-bis-(hydroxyimino)-1,2,9,10-hydroxy-4,7-dithiadecane (LH2), with bis-(thiopropandiol) moieties attached to the oxime. Thiopolyalcohol groups containing two different heteroatoms (-S- and -O-) serve as weak exocyclic binding sites for Pd+2 and Ag+ ions. Novel mononuclear (LH)(2)M, (M = Ni-II, Cu-II, Co-II, Mn-II and Fe-II), homodinuclear (LH)(2)(UO2)(2)(OH) and heterotrinuclear (LH)(2)MM2' (M = Ni-II and M' = Pd-II and Ag-I) species have been obtained with the metal: ligand ratios of 1:2, 2:2, and 3:2 respectively. Metal ions coordinate through N,N of the oxime and S,O donor sites of the peripherally attached groups in the presence of the base. The heterotrinuclear complexes were prepared by the interaction of the mononuclear complex, (LH)(2)Ni, with Pd(C5H5)(2) and AgNO3 in an appropriate solvent. The complexes were characterized by elemental analysis, H-1-n.m.r., u.v.-vis. spectroscopy, FT-IR., and by f.a.b-m.s. The redox properties of the complexes were studied by cyclic voltammetry.
Keywords: TRANSITION-METAL COMPLEXES; DISCOTIC LIQUID-CRYSTALS; VIC-DIOXIME; CHEMISTRY; MESOMORPHISM; MONONUCLEAR; COPPER(II); PALLADIUM(II); PLATINUM(II); TECHNETIUM